Influence of Brand Awareness, Brand Image, and Trust Against Kopi Kenangan Purchasing Decisions in West Jakarta - Nurul Islahiyah; Andyan Pradipta Utama (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This research aims to investigate the impact of brand recognition, brand image, and trust on purchase decisions for Kopi Kenangan, a popular coffee brand in West Jakarta. The study used purposive sampling to select 150 respondents from the Kopi Kenangan customer community, and data was collected through a survey questionnaire. The Partial Least Squares (PLS) technique was used to analyze the data. The study found that brand awareness, brand image, and trust have a significant and positive effect on customers' purchase decisions. The results of this study provide valuable insights into the factors that influence customer loyalty and purchase behavior in the coffee industry.